Electromyographic evaluation of spine and lower extremity muscles during repeated and sustained bodyweight deep-squat - Agarwal, Bela Manish (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Squat is a preferred exercise included in strengthening and rehabilitation protocols due to its ability to recruit large muscles of the spine and lower extremities. Speed of performing movement and regular practice are known to influence muscle activation. However, muscle activation during fast-repeated bodyweight deep-squat and sustained deep squat remains less explored. Aim of Study. This study aimed at exploring muscle activation during fast and sustained bodyweight squat and observing the effect of habitual squat exposure on spine and lower extremity muscle strength and activation. Material and Methods. Forty healthy adults (30-45 years), with varying daily squat exposure, were recruited for this cross-sectional study following an institutional ethical approval. Superficial electromyography of the erector spinae, rectus abdominis, gluteus maximus, gluteus medius, vastus lateralis, biceps femoris and the gastrocnemius was recorded during a single controlled squat, repeated fast squat and sustained squat. Muscle strength was evaluated using a trunk-leg dynamometer. Results. Higher muscle activity was observed during the ascent phase (81-240% MVC) and the descent phase (76-292% MVC) of a single squat, whereas the sustaining squat demanded low muscle activity (27-58% MVC). Repeated fast squatting elicited 2.5-10 times greater muscle activation than sustained squat. Muscle activity did not vary significantly among people with varying squat exposure. A moderately strong negative correlation was observed between deep squat repetitions and age (r = –0.710,p ≤ 0.001), whereas a moderate positive correlation was observed between deep squat repetitions and force developed during trunk and leg dynamometry (r = 0.610, p < 0.001,r = 0.654, p < 0.001, respectively). Substantial co-activation of the erector spinae–rectus abdominis, biceps femoris–vastus lateralis and gluteus maximus–gluteus medius was observed during fast repeated squat. Conclusions. Repeated, dynamic, bodyweight deep-squatting exercises elicited greater muscle activation compared to sustained squat. Exercises over and above habitual activities of daily living involving sustained squatting are essential to obtain greater benefits in muscle strength.